2014
DOI: 10.1177/0960327114530744
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear factor erythroid 2-related factor 2 rescues the oxidative stress induced by di-N-butylphthalate in testicular Leydig cells

Abstract: Aim: This study aimed to determine whether nuclear factor erythroid 2-related factor 2 antagonized the oxidative stress induced by di- N-butylphthalate (DBP) in testicular Leydig cells. Methods: Mouse TM3 testicular Leydig cells were treated with Nrf2 knockdown (KD) or overexpression in the presence and absence of DBP. Oxidative profiles were examined. Nrf2 target antioxidant genes were studied, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…SFN is a strong stimulant for Nrf2 and could exert potent antioxidant activity by activating Nrf2 . We first found that SFN induced similar extent of Nrf2 level to lentiviral Nrf2 overexpression and was paralleled with down‐regulation of KEAP1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…SFN is a strong stimulant for Nrf2 and could exert potent antioxidant activity by activating Nrf2 . We first found that SFN induced similar extent of Nrf2 level to lentiviral Nrf2 overexpression and was paralleled with down‐regulation of KEAP1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, we suggest that DBP may cause testis injuries via oxidative stress. Importantly, we have previously carried out a series of experiments by stimulation of DBP on a cell model, and have found that DBP could cause testicular oxidative stress injury and antioxidant drugs might resist this damage [ 7 ]. Therefore, we used the pregnant mice as a research model to study the impact of exposure to DBP and explore the protective effects of SFN.…”
Section: Discussionmentioning
confidence: 99%
“…Amid all organs, DBP has the highest affinity for testes and induces the oxidative stress injury, causing male reproductive dysfunction [ 5 , 6 ]. Our previous studies have suggested DBP could induce oxidative stress injury in testicular Leydig cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 'tube restraint test' was carried out and a significant change in the latency to the first bite and in the number of targets biting by the Pb treated female offspring. Recently other report suggested that the aggressive behaviour of mice was increased after exposing to lead acetate in their drinking water [18]. Anxiety is generally described as a physiological, behavioural and psychological state induced in humans and animals by a threat to well-being, potential or either actual.…”
Section: Social and Anxiety Behaviourmentioning
confidence: 99%